Effect of gender on blood pressure and heart rate variability during increasing intensities of isometric hand grip exercise in untrained adults / Faatihah Adeyinka Niyi-Odumosu and Mohammed Shahabu Meah - Niyi-Odumosu, Faatihah Adeyinka; Meah, Mohammed Shahabu (Universiti Teknologi MARA, 2023)
Gender influences blood pressure (BP) and heart rate variability (HRV). The purpose of this study was to investigate the influence of gender on BP and HRV during increasing intensities of isometric hand grip (IHG) exercise. Nineteen (n=19) (10 males, 9 females) participants aged 25.7±0.9 and 27.0±0.6 years (Mean± SEM), with height and weight of 173.4±3.1 cm, 72.8±3.7kg and 160.9±1.6 cm, 59.3±3.4 kg volunteered after ethical approval. BP, HRV and maximum voluntary contraction (MVC) was measured at rest. Thereafter, participants underwent 30% MVC for 2 minutes during which BP and HRV was taken with 10 minutes rest. Contractions were amplified to 35, 40, 45% MVC. One-Way ANOVA compared Mean±SEM values at 95% significance. The systolic blood pressure (SBP) increased significantly in females (p<0.001) than males (p<0.01); diastolic blood pressure (DBP) increased significantly in both gender (p<0.001); average number of heart beats increased significantly in males (p<0.001) than females (p<0.01); significant increase in LF/HF ratio in females (p<0.01) but not in males. However, there was no significant difference in the standard deviation of N-N interval (SDNN), low frequency (LF), high frequency (HF), very low frequency (VLF), root mean square of standard deviation (RMSSD), total frequency power (TFP), proportion of numbers of pairs of successive intervals (Pnn50) in both genders. This study may suggest a higher sympathetic influence (following rise in SBP and LF/HF ratio) in females than males during IHG exercise.